Essential Regions of Saccharomyces cerevisiae Telomerase RNA: Separate Elements for Est1p and Est2p Interaction - Livengood, April J. (American Society for Microbiology, 2002)
The Saccharomyces cerevisiae telomerase RNA subunit is encoded by the TLC1 gene. A selection for viable alleles of TLC1 RNA from a large library of random deletion alleles revealed that less than half (∼0.5 kb of the ∼1.3-kb RNA) is required for telomerase function in vivo. The main essential region (430 nucleotides), which contains the template for telomeric DNA synthesis, was required for coimmunoprecipitation with Est1p and Est2p. Furthermore, the subregion required for interaction with Est1p, the telomerase recruitment subunit, differed from those required for interaction with Est2p, the reverse transcriptase subunit. Two regions of the RNA distant from the template in the nucleotide sequence were required for Est2p binding, but the template itself was not. Having the RNA secured to the protein away from the template is proposed to facilitate the translocation of the RNA template through the active site. More generally, our results support a role for the telomerase RNA serving as a scaffold for binding key protein subunits.